Theoretical investigation of the magnetocaloric effect of La0.7(Ba, sr)0.3MnO3 compound at room temperature with a second-order magnetic phase transition. Issue 9 (November 2015) - Tlili, R.; Omri, A.; Bejar, M.; Dhahri, E.; Hlil, E.K.
Abstract: In this paper, the prediction of magnetic and magnetocaloric properties of La0.7 (Sr, Ba)0.3 MnO3 (LSBMO) compound have been conducted using a phenomenological model. Indeed, the investigation of magnetic properties has revealed that the sample exhibits a paramagnetic to ferromagnetic phase transition. Interestingly, the Curie temperature ( T C ) was found to decrease from 322 to 300 K with the decrease of magnetic fields. Moreover, the magnetocaloric data displays a large value of the magnetic entropy change, 1.5 J kg −1  K −1 under an applied magnetic field change of 20 kOe, which increases with the increase of the applied magnetic field, making it a promising compound for ecologically-friendly magnetic refrigeration at room temperature. Finally, the construction of the universal curve of the magnetic entropy change proves that the studied manganite undergoes a second order magnetic phase transition.